Jean Aubouin et les chaînes de montagnes : des observations aux synthèses. L’itinéraire scientifique d’un géologue au rayonnement international - Ferrière, Jacky; Faure, Michel (Comptes Rendus. Géoscience)
Jean Aubouin’s scientific itinerary spans many decades since the 1950s. Several periods can be recognized in this research continuum, but the consistency of the approach to understand mountain ranges and orogenic processes is a striking feature. After an attempt to decipher the main operating rules of orogens, the emergence of Plate Tectonics theory led Jean Aubouin to turn to the Oceans without neglecting the continents, party carried out by its first and second generation “pupils”. His many responsibilities, his election to the Academy of Sciences, then its presidency, never affected his determination to continue his research on orogeny.